Fabrication of porphyrin-based aggregates through modulating hexapeptide secondary conformation. (March 2021) - Liu, Ruihong; Liu, Dongzhi; Meng, Fancui; Li, Wei; Wang, Lichang; Zhou, Xueqin
Abstract: The stacking mode of aggregates directly determines the morphology and properties of assemblies. However, how the peptide secondary confirmation affects the arrangement of artificial photosynthetic supramolecules is still ambiguous. Herein, a porphyrin-hexapeptide supramolecule TPP-Ala-Ala-MV was synthesized to investigate the effect of its secondary conformation on the stacking mode and morphology of aggregates. Nanosheets, nanospheres and nanotubes were obtained from TPP-Ala-Ala-MV at different pH conditions. It was revealed that the pH condition influences not only the aggregation of porphyrin cores, but also its secondary conformation composition. Both experimental and computational results discover that the hexapeptide α-helix conformation has the strongest intramolecular hydrogen bond interaction, whereas no intermolecular hydrogen bond forms in β-sheet conformation. The inclination to J-aggregation, as well as the weak intermolecular interaction among hexapeptide turn conformation, leads to the formation of nanosheets. The inclination to H-aggregation coupled with the strong intermolecular interaction among hexapeptide β-sheet conformations promotes the formation of a highly packed structure, resulting in aggregates of nanosphere or nanotube shape. These results pave the way for the development of artificial photosynthesis systems by regulating the aggregate structures of porphyrin-peptide supramolecular systems. Highlights: A novel porphyrin-hexapeptide supramolecule was synthesized and characterized. The pH conditions can change the hexapeptide secondary conformation composition. Hexapeptide turn conformations and porphyrin J-aggregation result in nanosheets. β-Sheet hexapeptide and H-aggregated porphyrin lead to nanospheres or nanotubes.